Comparing the diffusive gradient in thin film (DGT) method with water and ammonium-acetate-lactate for P extraction and extractable P required for maximum cereal yield using long-term field experiments - Mesmer, Cornelia (2017)
Using more phosphorus fertilizer than needed generates unnecessary costs for farmers and can lead to eutrophication of surface waters. Up to now, most country-specific soil tests to determine P plant-availability use chemical extractions that often extract P from non-plant available pools and are not suitable for all soil types. The diffusive gradient in thin film (DGT) method was introduced as a mechanistic surrogate of plant-available phosphorus using water and diffusion in order to quantify P release. In this study, the DGT method was examined and compared with water and ammonium-acetate-lactate extraction. Water extractable P and P-DGT were highly correlated. In order to determine critical thresholds for maximum yields, soil samples from six sites from a long-term field experiment in Sweden and from one site in Switzerland, cultivated with cereals and fertilized with different P rates were used. Piecewise regression and the Mitscherlich model were used to fit extracted P data to relative yields and the piecewise regression provided better fits. Determination of DGT seemed to be superior over the two other P extraction methods to determine critical threshold values for maximum yield but all were useful.